The practical integration of a hybrid model of ultrasound‐guided peripheral venous access in a large apheresis center. Issue 4 (2nd July 2020) - Barth, David; Nemec, Rosaleen M.; Cho, Dennis D.; Slomer, Adam; Cojocari, Eduard; Kim, Kyuho; McLean, Lianne D.; Patriquin, Christopher J.
Abstract: Background: Apheresis treatments require adequate venous access using peripheral intravenous (PIV) catheterization or central venous catheters (CVC). Ultrasound‐guided PIV (USGPIV) can be used to decrease the need of CVC insertions for apheresis procedures. Method: A hybrid model of USGPIV and standard of care (SOC) for PIV access was developed. Nurses performed USGPIV on all patients considered for PIV access if felt SOC PIV access was not possible. Information was collected regarding nurses' confidence with access, number of attempts required, site of access, complications, and need for CVC. Results: In all, 226 PIV access attempts were made during a 2‐month period. All apheresis procedure types were represented. A total 65% were accessed by SOC and 35% by USGPIV. USGPIV was successful on first try on 90% draw/inlet access and 87% successful on first try on return access. Access above the antecubital fossa was required in 31% of USGPIV for draw/inlet veins, and 22% of return veins. Nurses' confidence with accessing PIV was increased by USGPIV, based on 7‐point Likert scale assessments. During the recording period, 2/226 (0.9%) apheresis procedures required a CVC. In a separate cohort of only hematopoietic progenitor cell collections, CVC insertion was required in 44/238 (18.5%) patients, in 7 months prior to adoption of USGPIV and 5/152 (3.3%) patients in 7 months following adoption of USGPIV. Conclusion: A hybrid model of using SOC and USGPIV for PIV access for apheresis procedures resulted in decreased need for CVC access, high levels of successful initial access attempts, and increased nursing confidence in PIV access.